2021
DOI: 10.1111/ijpo.12844
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal and infant metabolite profiles with foetal growth and the odds of adverse birth outcomes

Abstract: Background: Adaptations in maternal and foetal metabolic pathways may predispose to altered foetal growth and adverse birth outcomes.Objective: To assess the associations of maternal early-pregnancy metabolite profiles and infant metabolite profiles at birth with foetal growth from first trimester onwards and the odds of adverse birth outcomes.Methods: In a prospective population-based cohort among 976 Dutch pregnant women and their children, serum concentrations of amino acids, non-esterified fatty acids (NEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In a prospective study of 976 Dutch pregnant women and their children, Voerman and colleagues observed several individual maternal phospholipids during early pregnancy significantly associated with femur length and head circumference in the third trimester and weight and head circumference at birth. 11 Morillon et al. performed a lipidomics analysis in a case–control study of 40 SGA cases and 40 controls and showed an association between elevated maternal levels of GPL at GW 20 and higher risk of SGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study of 976 Dutch pregnant women and their children, Voerman and colleagues observed several individual maternal phospholipids during early pregnancy significantly associated with femur length and head circumference in the third trimester and weight and head circumference at birth. 11 Morillon et al. performed a lipidomics analysis in a case–control study of 40 SGA cases and 40 controls and showed an association between elevated maternal levels of GPL at GW 20 and higher risk of SGA.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Advanced lipidomics technologies permit the high-throughput assessment of a large number of lipid species in human bio-samples. Recently, maternal lipidomic profiles in plasma or serum samples have been associated with GDM 7 and perinatal outcomes, such as intrauterine growth restriction, pre-term birth, 8 birth weight (BW), 9 , 10 , 11 small size-for-gestational age at birth (SGA), 12 , 13 and large size-for-gestational age at birth (LGA). 10 …”
Section: Introductionmentioning
confidence: 99%
“…While it has been described that lyso-PC is, for example, decreased in Alzheimer’s disease patients brains and in tissue of mouse models [ 62 , 63 ], we were not able to identify reports on its distinctive role in late brain development. Higher serum levels of acyl-lyso-PC and alkyl-lyso-PC were associated with higher weight, length, and head circumference in infants at birth [ 64 ], probably pointing at a beneficial effect. The cytosolic calcium-dependent phospholipase A2 (cPLA2) seems to preferably target phosphatidylcholine, resulting in release of lyso-PC and arachidonic acid (ARA) (for a review on PLA2: [ 65 ]).…”
Section: Discussionmentioning
confidence: 99%